Hierarchical Porous O‐Doped g‐C3N4 with Enhanced Photocatalytic CO2 Reduction Activity. Issue 15 (3rd February 2017) - Fu, Junwei; Zhu, Bicheng; Jiang, Chuanjia; Cheng, Bei; You, Wei; Yu, Jiaguo
Abstract : Artificial photosynthesis of hydrocarbon fuels by utilizing solar energy and CO2 is considered as a potential route for solving ever‐increasing energy crisis and greenhouse effect. Herein, hierarchical porous O‐doped graphitic carbon nitride (g‐C3 N4 ) nanotubes (OCN‐Tube) are prepared via successive thermal oxidation exfoliation and curling‐condensation of bulk g‐C3 N4 . The as‐prepared OCN‐Tube exhibits hierarchically porous structures, which consist of interconnected multiwalled nanotubes with uniform diameters of 20–30 nm. The hierarchical OCN‐Tube shows excellent photocatalytic CO2 reduction performance under visible light, with methanol evolution rate of 0.88 µmol g −1 h −1, which is five times higher than bulk g‐C3 N4 (0.17 µmol g −1 h −1 ). The enhanced photocatalytic activity of OCN‐Tube is ascribed to the hierarchical nanotube structure and O‐doping effect. The hierarchical nanotube structure endows OCN‐Tube with higher specific surface area, greater light utilization efficiency, and improved molecular diffusion kinetics, due to the more exposed active edges and multiple light reflection/scattering channels. The O‐doping optimizes the band structure of g‐C3 N4, resulting in narrower bandgap, greater CO2 affinity, and uptake capacity as well as higher separation efficiency of photogenerated charge carriers. This work provides a novel strategy to design hierarchical g‐C3 N4 nanostructures, which can be used as promising photocatalyst for solar energy conversion. Abstract : Metal‐free g‐C3 N4 with layered structure has tremendous potential in photocatalytic solar‐to‐fuels conversion. A novel strategy is applied to design hierarchical O‐doped g‐C3 N4 nanotubes with excellent activity for photocatalytic CO2 reduction into hydrocarbon fuels (CH3 OH).